As “eleições do cacete” e o problema da manipulação eleitoral no Brasil monárquico - Saba, Roberto N. P. F. (2022)
For a long time historians have studied elections in the Brazilian Empire through the analysis of the corrupt practices carried out by the central government or the local potentates, who manipulated the polls and perverted the free choice of voters and electors. Recent works, however, are reconsidering this topic, going beyond the exposition of corrupt practices and searching for the significance of the electoral process for the historical agents involved in it. The present article aims to contribute to this recent debate through the analysis of the infamous “eleições do cacete”, which happened in 1840. By analyzing petitions sent to the Chamber of Deputies by citizens who claimed to be victims of the government’s truculence, it is possible to understand how denouncing electoral manipulation was part of the nineteenth-century political juggling. These petitions elucidate how citizens of the Empire were capable of understanding the representative government under which they lived and how the contemporary political leaders made use of petitioning to conduct their disputes.